The Pemberdayaan Masyarakat dengan Aktivitas Leisure - Endang Sri Wahyuni; Roh Hastuti Prasetyaningsih (Poltekkes Kemenkes Surakarta, 2020)
Background: The temporary suspension of Posyandu Elderly activities has resulted in a decline in the role and function of health cadres in monitoring the health of the elderly. This is also accompanied by a decrease in the health condition of the elderly because they cannot carry out social leisure activities, which are generally carried out in the Elderly Posyandu activity forum. The purpose of this community service activity is so that cadres can optimize their role and function in monitoring the health of the elderly during a pandemic. The health of the elderly is maintained through the leisure activity program provided. Meanwhile, the elderly who are affected by Covid-19can still be guaranteed their basic needs through the distribution of existing assistance. Methods: For cadres are given counseling and training on the role of health cadres during a pandemic. Elderly people are given leisure activity programs carried out both individually and in small groups, facilitating leisure activities, counseling on preventing the spread of Covid-19, and distributing basic needs assistance for elderly people affected by Covid-19. Results: Kader has demonstrated its performance in monitoring the health of the elderly and helping facilitate elderly leisure activities. Elderly people can do leisure activities during the pandemic so they don't feel lonely anymore, feel happy because they can meet other elderly people of their age, don't feel overly afraid, and can participate in social activities to support the basic needs of elderly people affected by Covid-19. The awareness of the elderly in applying the new health norms has also increased. Conclusion: Of community empowerment with leisure activities during the pandemic can be realized thanks to cross-sectoral cooperation. This activity requires a follow-up in the form of evaluation and monitoring of existing programs.